Canva Media Implementation for Enhancing Grade Four Civic Education Learning Outcomes - Niluh Chixa Widiani; Yusdin Bin. M. Gagaramusu; Pahriadi Pahriadi; Arif Firmansyah; Muhammad Nazimuddin Al Kamil; Surahman Wilade (Journal of Innovation and Research in Primary Education, 2026)
Traditional teaching methods in Pancasila and Civic Education (PPKn) often result in passive learning and low student engagement, particularly in rural elementary schools. This study investigated the effectiveness of Canva media implementation in enhancing fourth-grade students' PPKn learning outcomes at SDN 2 Dolo. A Classroom Action Research design following the Kemmis and McTaggart model was employed across two intervention cycles. Thirteen fourth-grade students (8 males, 5 females) participated in the study. Data were collected through pre-tests, post-tests, structured observation sheets for teacher and student activities, and documentation. Quantitative data were analyzed using individual and classical absorption capacity formulas, while qualitative data were analyzed descriptively and categorized. Student mastery rates increased substantially from 15.38% (pre-test) to 38.46% (Cycle I) and 92.30% (Cycle II), with class average scores improving from 58.46 to 86.15. Teacher activity improved from 69.53% (Fair) to 93.75% (Very Good), while student engagement increased from 76.78% (Good) to 94.64% (Very Good). Classical learning completeness in Cycle II (92.30%) exceeded the 75% success criterion. Systematic implementation of Canva media significantly enhances PPKn learning outcomes by transforming abstract civic concepts into concrete, visual, and interactive learning experiences. The cyclical action research approach proved effective for instructional improvement and teacher professional development.